2019
DOI: 10.1001/jamaneurol.2018.4165
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Clinical Complications, Case-Fatality Risks, and Risk Factors in Endovascular and Neurosurgical Treatment of Unruptured Intracranial Aneurysms

Abstract: IMPORTANCEThe risk of procedural clinical complications and the case-fatality rate (CFR) from preventive treatment of unruptured intracranial aneurysms varies between studies and may depend on treatment modality and risk factors. OBJECTIVE To assess current procedural clinical 30-day complications and the CFR from endovascular treatment (EVT) and neurosurgical treatment (NST) of unruptured intracranial aneurysms and risk factors of clinical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 142 publications
2
127
2
2
Order By: Relevance
“…By contrast, we found that ischemic stroke was less frequent in the context of SAC or BAC as compared to surgical clipping alone among patients with unruptured IA. This finding is contrary to a previously conducted systematic review and meta-analysis of 114 studies (106,433 patients with 108,263 aneurysms), whereby the use of stenting or SAC in the context of endovascular therapies increased the complication rates by nearly two to threefold [27]. In a previously conducted study, McDonald et al performed secondary analyses of the 2004-2008 NIS database to compare in-hospital outcomes of endovascular coiling with and without adjunctive stenting among patients with unruptured IA [28].…”
Section: Discussioncontrasting
confidence: 97%
“…By contrast, we found that ischemic stroke was less frequent in the context of SAC or BAC as compared to surgical clipping alone among patients with unruptured IA. This finding is contrary to a previously conducted systematic review and meta-analysis of 114 studies (106,433 patients with 108,263 aneurysms), whereby the use of stenting or SAC in the context of endovascular therapies increased the complication rates by nearly two to threefold [27]. In a previously conducted study, McDonald et al performed secondary analyses of the 2004-2008 NIS database to compare in-hospital outcomes of endovascular coiling with and without adjunctive stenting among patients with unruptured IA [28].…”
Section: Discussioncontrasting
confidence: 97%
“…The reported overall complications rate of endovascular treatment for intracranial stenosis is around 10%, and the unfavorable clinical outcome rate is around 5% [24][25][26]. The reported complications rate of endovascular treatment for UIAs is 4.9% [27] and unfavorable outcome is around 4.8% [28]. In this cohort, UIA embolization and intracranial stenosis angioplasty related complication is 4 (6.3%) and 2 (5.0%) respectively, and total unfavorable clinical outcome is 4 (5.4%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis and systematic review of both neurosurgical and endovascular interventions 25 examined 114 studies comprising 106 433 patients and 108 263 UIAs. There were 74 endovascular therapy studies with a complication rate of nearly 5% (95% CI 4% to 6%) and case fatality risk of 0.3% (95% CI 0.2% to 0.4%).…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…A systematic review and meta-analysis of 54 neurosurgical studies 25 reported a complication rate of 8.34% (95% CI 6.25% to 11%) and a case fatality rate of 0.1% (95% CI 0% to 0.2%). Factors associated with complications included age >50 years, female sex, coagulopathy, anticoagulation, smoking, hypertension, diabetes mellitus, congestive heart failure, posterior circulation location, aneurysm calcification and aneurysm size >12 mm.…”
Section: Neurosurgical Treatmentmentioning
confidence: 99%